Functions of Some Sirtuins and Their effect on Type 2 Diabetes Mellitus in Iraqi Patients - Shamkhi, Rasha Jaber (Central Asian Journal of Medical and Natural Science, 2025)
This paper intended to estimate the interrelationship among the SIRT1 gene expression and type 2 diabetes mellitus (T2DM) in a sample of individuals from Wasit City, Iraq in collaboration with AL-Karama Teaching Hospital. A total of 60 participants (40 diabetic patients and 20 healthy controls), aged between 40 and 70 years, were enrolled. Blood samples were analyzed using RT-PCR to assess gene expression and ELISA to measure protein concentration in serum .SIRT1 gene expression was significantly upregulated in diabetic patients, as indicated by a lower ΔCt value, with strong statistical significance (P = 0.001). No significant difference in SIRT1 protein levels in the serum among the diabetic and controlling groups (P = 0.85). No significant gender-based differences were noticed in SIRT1 protein concentrations . The findings suggest a notable increase in SIRT1 gene expression in individuals with T2DM, potentially indicating a regulatory role of this gene in the disease. However, the lack of corresponding changes in protein levels warrants further studies to clarify the underlying mechanisms.